CHEMICAL FEATURES OF FOREWING SCALES OF Leptosia nina Fabricius, 1793 (Lepidoptera: Pieridae) (Applied Biological Research, 2024)
The functional groups have a vital role in insect physiology, behaviour, and  adaptation to the environment and are crucial in biomimetics to replicate  and adapt biological functions for diverse use ranging from medicine to  material science and energy technologies. A study was conducted on Leptosia  nina forewing scales to assess its chemical composition spectra using Fourier  Transform Infrared Spectroscopic (FTIR) analysis. The identified functional groups from dorsal white, dorsal black spot, ventral white and ventral black spot areas of L. nina forewing composed of alcohols, phenols, aldehydes, aliphatic amine, alkanes, alkenes, alkyl halides, alkynes, aromatic groups,carboxylic acid groups, nitro compounds, amines, ester and ether with various  stretches. The spectra showed minor variations in peaks in the four regions studied. The  study is the first record revealing the functional groups of L. nina forewing  scales.
Keywords: Chemical composition spectra; forewing; FTIR spectroscopy; functional groups; Leptosia nina; scales